2012
DOI: 10.1088/1748-9326/7/1/015601
|View full text |Cite
|
Sign up to set email alerts
|

Environmental changes and violent conflict

Abstract: This letter reviews the scientific literature on whether and how environmental changes affect the risk of violent conflict. The available evidence from qualitative case studies indicates that environmental stress can contribute to violent conflict in some specific cases. Results from quantitative large-N studies, however, strongly suggest that we should be careful in drawing general conclusions. Those large-N studies that we regard as the most sophisticated ones obtain results that are not robust to alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(91 citation statements)
references
References 71 publications
1
86
0
Order By: Relevance
“…However, research to date is partial in that it has been mainly qualitative, and the quantitative approaches that have been implemented (i.e., statistical and econometrical models) have proven to be reliable only when analysing specific case studies [71]. Previous studies, like those of Berazneva and Lee [70] and Bellemare [61], have found a clear connection between the increase in food prices and the increase in food riots, with the second author being able to prove a causality relationship.…”
Section: Introductionmentioning
confidence: 99%
“…However, research to date is partial in that it has been mainly qualitative, and the quantitative approaches that have been implemented (i.e., statistical and econometrical models) have proven to be reliable only when analysing specific case studies [71]. Previous studies, like those of Berazneva and Lee [70] and Bellemare [61], have found a clear connection between the increase in food prices and the increase in food riots, with the second author being able to prove a causality relationship.…”
Section: Introductionmentioning
confidence: 99%
“…While this result weakens the finding of Burke et al in a specific way, it was widely overinterpreted as disproof of the Burke et al finding (Bernauer et al 2012;Scheffran et al 2012). The uncertainty in Buhaug's estimates are large, causing them to not be statistically distinguishable from the original estimate of Burke et al and preventing the study from ruling out large effects of climate on conflict.…”
Section: Africa-only Datamentioning
confidence: 53%
“…In recent articles, Bernauer et al (2012), Gleditsch (2012) and Scheffran et al (2012) describe some recent progress in this literature and arrive at largely different conclusions than those presented here. We maintain this discrepancy is primarily due to (1) our use of different and more stringent methodological standards, and (2) we examine more data.…”
Section: Introductionmentioning
confidence: 52%
“…Review studies until 2013 concluded with that there are limited links between climate anomalies and collective violence [30][31][32][33][34]. A meta-study and accompanying literature reviews by Hsiang, Burke and Miguel found a substantial and significant link [35][36][37].…”
Section: The Climate-conflict Debate Pre-2014mentioning
confidence: 99%